mergency Training Due To Heart Arrest And Fractures Around The Location Of The Umbul Ponggok Tourism - Firman Faradisi; Nurul Aktifah; Dwi Fijianto (Prosiding University Research Colloquium, 2022)
Indonesia is an archipelagic country with diverse geographical conditions, and has various tourist attractions that are crowded with visitors. Water tourism in Ponggok is one area that is often visited and passed by many vehicles. this increases the risk of accidents that can lead to emergency cardiac arrest and fractures from accidents. The problem that arises is, not all sellers and residents around the tourism object understand and are able to provide first aid correctly. The purpose of this training is to teach emergency first aid for cardiac arrest and fractures. Respondents who participated in the service were 25 people. The results of the pre test found that respondents with a moderate level of knowledge were 24%, while respondents who had a low level of knowledge were 76%. The results of the post test show a change where respondents who have a high level of knowledge are 36%, and respondents with a moderate level of knowledge are 64%. From the results of this training, the community has more confidence and more confidence in handling emergencies that occur.